Penerapan Manajemen Sarana dan Prasarana Pendidikan di Sekolah Dasar - Ikramullah, Ahmad Saleh; Kafrawi, Kafrawi; Armizi, Armizi; Napratilora, Martina; Susanti, Erma (Mitra PGMI: Jurnal Kependidikan MI, 2023)
The purpose of this study was to determine the application of management of educational facilities and infrastructure at SDN 002 Tembilahan Kota, and the factors that influence it. The population in this study was the principal and all school personnel, totaling 29 people at the 002 Tembilahan City State Elementary School. The data in this study were collected using questionnaires, interviews and documentation techniques. Furthermore, the collected data is analyzed using the percentage formula. From the results of the study, it can be concluded as follows: The implementation of educational facilities and infrastructure at the 002 Tembilahan City State Elementary School, reached a score of 79.54%, and was categorized as good, because the figure of 79.54% lies in the 61% - 80% interval. The factors that influence the implementation of facilities and infrastructure management at the 002 Tembilahan State Elementary School are as follows: planning the needs of educational facilities and infrastructure, procurement of educational facilities, storage of facilities and infrastructure, inventory, maintenance and utilization of educational infrastructure facilities, and removal of damaged facilities and infrastructure.